Flight risk : a novel - Priest, Cherie (Priest, Cherie. Booking agents novel., 2022)
"Inconsistent psychic Leda Foley and Seattle detective Grady Merritt return to solve the case of a missing couple in this sequel to the "delightful" (The New York Times Book Review) mystery Grave Reservations"--